Maturação, antropometria, composição corporal e desempenho físico de praticantes de judô do município de Marechal Cândido Rondon - Pr - Vitor Henrique Vassoler; Edilson Hobold (Universidade Estadual do Oeste do Paraná, 2018)
Adolescence is a life period of utmost importance in physical and maturational changes. Individuals of the same chronological age but advanced maturational stage can present sports advantages due to a greater increase in muscle mass and strength. The objective of this research was to investigate somatic maturation through peak high velocity (PHV) in male judo practitioners, aged 10 to 17 years-old from the city of Marechal Cândido Rondon (PR). Thirty-five judokas were intentionally selected to participate in the study. The assessment included anthropometry, body composition, physical fitness and a sport specific judo test. The statistical analyzes were calculated using the SPSS software for Windows® - v. 15.0. The results showed that PHV occurred at the age of 13.83 years. The anthropometric variables of body mass, height, and trunk-cephalic height presented a constant linear growth as the somatic maturation progressed. Regarding the variables of body composition, it was verified that with the advancement of the maturational phase the percentage of fat had a constant decrease in values. In turn, lean body mass showed a linear growth. Regarding the physical performance variables, the tests of explosive strength of lower limbs, abdominal endurance, speed, upper limbs strength/resistance and flexibility increased linearly at the PHV, however, the specific sports test reached its best index post-PHV. In conclusion, for the present sample, PVC showed a tendency to influence physical growth, body composition and physical performance in most of the tests to which the judokas were submitted.